Respecting the values of the constitution: Integration in the community of value(s) - Manser-Egli, Stefan (Frontiers in Political Science, 2023)
Current integration regimes increasingly require migrants to share constitutional values. Taking Switzerland as a case study, the paper analyzes this integration requirement based on the legal framework, problem-centred interviews among public authorities and street-level bureaucrats, case files and case law. It argues, first, that the requirement re/produces the social imaginary of society as a community of value(s), which in turn legitimizes aggressive integrationism. Second, the values concerned are to a very large extent an empty signifier that can be filled with almost any cultural stuff. This is the case, third, as long as the reference to abstract universal liberal principles is maintained, revealing a distinctly liberal boundary making. In conclusion, the value requirement turns out to be old-fashioned cultural assimilation in a contemporary liberal guise, positing liberal values as an achieved feature of modern societies, shared by all members of the community of value(s).